Introducing Automated Public Lighting Using Solar Cells in Giri Mekar Village: A Workshop on Equipment Familiarization and Maintenance for the Youth and Karang Taruna - Wawan Purnama; Resa Pramudita; Muhammad Adli Rizqulloh; Neris Peri Ardiansyah; Roer Eka Pawinanto; Jaja Kustija (Institut Teknologi Nasional, Bandung, 2023)
In Giri Mekar Village, the challenge of public street lighting has become a critical issue affecting the daily lives of its residents. Identifying the need for a sustainable solution, an initiative was launched to introduce automatic lighting technology based on solar cells. Through specially designed socialization and training activities, the youth and members of Karang Taruna were engaged to understand, operate, and maintain this lighting system. The training methodology included theoretical sessions on solar cells, equipment demonstrations, and hands-on installation sessions. As a result of these activities, participants demonstrated significant skill enhancement and understanding, as well as a commitment to implementing and maintaining this technology in their village. The overall initiative not only offered an efficient lighting solution but also promoted the concept of community empowerment in village infrastructure development.